Spatial Transformation of Agrarian Cultural Tourism in the Muria Volcano Region, Indonesia through Markerless Augmented Reality and Cross-Generational Empowerment - Eva Banowati; Efriyani Sumastuti; Juhadi Juhadi; Mu'arifuddin Mu'arifuddin; Muhammad Iqbal; Satya Budi Nugraha; Muhammad Guruh Bintang Wicaksana; Novianto Adhi Sucipta (Universitas Negeri Gorontalo, 2026)
This study examines the spatial transformation of agrarian cultural tourism in the Muria Volcano Region, Indonesia, through the integration of markerless augmented reality (MAR) and cross-generational community empowerment. Using a mixed-methods design, the research combines a quantitative survey of 150 agritourism-related micro, small, and medium enterprises (MSMEs) with qualitative data derived from focus group discussions, field observations, and an intensive empowerment and training programme involving a purposive subset of 35 MSME participants representing different generations. Quantitative analysis using PLS-SEM and IPMA explores the relationships between agrarian cultural values, business financial management, digital technology adoption, and profitability, while qualitative insights are used to interpret socio-spatial dynamics, learning processes, and local practices shaped through empowerment activities. The findings indicate that agrarian cultural values and digital technology adoption mediate how local communities engage with tourism spaces, while cross-generational empowerment enhances digital readiness and interpretive capacity. MAR contributes to spatial storytelling and visitor engagement by enabling interactive representations of cultural landscapes, although its implementation remains constrained by uneven digital skills and infrastructure. This study contributes to social and tourism geography by demonstrating how digital spatial media can support community empowerment and sustainable tourism development in peripheral volcanic landscapes. It also offers insights for geography education through its emphasis on spatial representation, place-based learning, and technology-mediated understanding of cultural landscapes in tourism contexts.